Implementasi Load Balancing Dengan Metode Equal Cost Multi-Path - MUHAMMAD FAUZI ZULKARNAEN; Muhamad Iqbal Isnaini (LPPM STMIK Lombok, 2018)
The availability of the Internet has already become a staple menu for business and educational institutions, one of which high school management informatics and computer (STMIK) Lombok, its role is already included in the category of primary from high school is, unfortunately, the Internet is today was still not reliable because it is often experiencing a lost connection to the network. This is quite disturbing and can degrade the performance of the object. Ideally, high school today must have an Internet network that reliably and can fulfill their role on an ongoing basis, is no exception tissue in the lab campus STMIK Lombok, and in cases like this there are some ways that can be applied either by replacing existing ISP today with the more reliably, or implement load balancing features for performance of load balancing is helpful in two consummation of a connection that is more stable due to the function of load banlance itself is used to divide the load (load) into multiple lines (links) so, the authors decided to propose solution in the form of two ISPs' internet network by means of load balancing using Equal Cost Multi-Path (ECMP) to resolve the above problems.